Household expectations and dissent among policymakers - Moritz Grebe; Peter Tillmann (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2022)
This paper studies the impact of dissent in the ECB's Governing Council on uncertainty surrounding households' inflation expectations. We conduct a randomized controlled trial using the Bundesbank Online Panel Households. Participants are provided with alternative information treatments concerning the vote in the Council, e.g. unanimity and dissent, and are asked to submit probabilistic inflation expectations. The results show that the vote is informative. Households revise their subjective inflation forecast after receiving information about the vote. Dissenting votes cause a wider individual distribution of future inflation. Hence, dissent increases households' uncertainty about inflation. This effect is statistically significant once we allow for the interaction between the treatments and individual characteristics of respondents. The results are robust with respect to alternative measures of forecast uncertainty and hold for different model specifications. Our findings suggest that providing information about dissenting votes without additional information about the nature of dissent is detrimental to coordinating household expectations.
Keywords: E52; E43; E32; 330; central bank communication; disagreement; inflation expectations; randomized controlled trial; survey